To find the solution to the system of equations, we can solve the equations simultaneously using either substitution or elimination.
Using the substitution method:
From the first equation, we can solve for x in terms of y:
3x + 3y = 15
3x = 15 - 3y
x = (15 - 3y)/3
x = 5 - y
Substituting this value of x into the second equation:
8x + 5y = 46
8(5 - y) + 5y = 46
40 - 8y + 5y = 46
-3y = 6
y = -2
Substituting the value of y back into the first equation:
3x + 3(-2) = 15
3x - 6 = 15
3x = 21
x = 7
Therefore, the solution to the system of equations is:
x = 7, y = -2.
So, the answer is B) x = 7, y = -2.
3x + 3y = 15
8x + 5y = 46
What is the solution to the system of equations above?
Responses
A x = -3, y = 6x = -3, y = 6
B x = 7, y = -2x = 7, y = -2
C x = 6, y = -4x = 6, y = -4
D x = -2, y = -6x = -2, y = -6
1 answer